Cinacalcet lowering of serum fibroblast growth factor-23 concentration may be independent from serum Ca, P, PTH and dose of active vitamin D in peritoneal dialysis patients: a randomized controlled study - Kim, Hyo Jin (BioMed Central, 2013)
BACKGROUND: Elevated serum level of fibroblast growth factor-23 (FGF23) is associated with adverse outcomes in dialyzed patients. OBJECTIVES: The CUPID study compared the efficacy of a cinacalcet-based regimen with conventional care (vitamin D and P binders) for achieving the stringent NKF-K/DOQI targets for peritoneal dialysis (PD) patients. Additionally, we analyzed change in FGF23 levels between two treatments to explore the cinacalcet effect in lowering FGF23. DESIGN: Multicenter, open-labeled, randomized controlled study. SETTING: Seven university-affiliated hospitals in Korea. PARTICIPANTS: Overall, 66 peritoneal dialysis patients were enrolled. INTERVENTION: Sixty six patients were randomly assigned to treatment with either cinacalcet + oral vitamin D (cinacalcet group, n = 33) or oral vitamin D alone (control group, n = 33) to achieve K/DOQI targets. CUPID included a 4-week screening for vitamin D washout, a 12-week dose-titration, and a 4-week assessment phases. We calculated mean values of iPTH, Ca, P, Ca x P, during assessment phase and final FGF23 to assess the outcome. MAIN OUTCOME MEASURES: Achievement of >30% reduction of iPTH from baseline (primary) and FGF23 reduction (secondary). RESULTS: 72.7% (n = 24) of the cinacalcet group and 93.9% (n = 31) of the control group completed the study. Cinacalcet group received 30.2 ± 18.0 mg/day of cinacalcet and 0.13 ± 0.32 μg/d oral vitamin D (P < 0.001 vs. control with 0.27 ± 0.18 μg/d vitamin D). The proportion of patients who reached the primary endpoint was not statistically different (48.5% vs. 51.5%, cinacalcet vs. control, P = 1.000). After treatment, cinacalcet group experienced a significant reduction in FGF23 levels (median value from 3,960 to 2,325 RU/ml, P = 0.002), while an insignificant change was shown for control group (from 2,085 to 2,415 RU/ml). The percent change of FGF23 after treatment was also significantly different between the two groups (− 42.54% vs. 15.83%, P = 0.008). After adjustment, cinacalcet treatment was independently associated with the serum FGF23 reduction. CONCLUSION: Cinacalcet treatment was independently associated with the reduction of FGF23 in our PD patients. TRIAL REGISTRATION: Controlled trials NCT01101113